Kemandirian Pangan Keluarga di Masa Pandemi dengan Pemanfaatan Lahan Pekarangan - Mohammad Azharudin; Putri Intani Aisa Masruil; Salma Fajriani Putri; Achmad Room Fitrianto (ABDI: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2022)
Indonesia until the first half of 2021 is still suffering from Covid-19 pandemic. The impact of Catasrophic affects all aspect, including economy. Many people are forced to lose their jobs so that they are unable to fulfill their daily needs, especially food and health needs. This problem also occurs in Bringinbendo village, Taman sub-district, Sidoarjo district, East Java. In order to overcome the economic difficulties that caused by covid 19, a frugal action and innovation needed to develop food and health security that originated from surrounding resourches. The Frugral action that has been take is planting their open space including house yard for vegetables. Through this program, the people of Bringinbendo village empowered and able to supply their daily need from the house yard and recuding the economic distress caused Covid-19.